1989
DOI: 10.1084/jem.169.6.2263
|View full text |Cite
|
Sign up to set email alerts
|

Putative amino acid sequence of HLA-DRB chain contributing to rheumatoid arthritis susceptibility.

Abstract: The association between HLA-DR4 and rheumatoid arthritis (RA) has been established in many ethnic groups. To clarify the determinant of susceptibility to RA, a polymorphic segment of the HLA-DRB gene was amplified in vitro by polymerase chain reaction and analyzed with oligonucleotide probes specific for the HLA-DR4 DNA sequences. A particular sequence encoding amino acids Gln70-Arg71-Arg72-Ala73-Ala74 showed a strong association with RA (p less than 0.005, relative risk 6.0). This amino acid sequence occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 19 publications
5
32
0
1
Order By: Relevance
“…DRBl"0405, which was associated with arthritis in the present study, is known to be a susceptibility allele for rheumatoid arthritis in the Japanese population (10). Recent analyses by a British group have also shown that the development of rheumatoid arthritis in MCTD patients is associated with DR4 or DRI excluding DRBl"C1103 (11).…”
Section: Discussionsupporting
confidence: 62%
“…DRBl"0405, which was associated with arthritis in the present study, is known to be a susceptibility allele for rheumatoid arthritis in the Japanese population (10). Recent analyses by a British group have also shown that the development of rheumatoid arthritis in MCTD patients is associated with DR4 or DRI excluding DRBl"C1103 (11).…”
Section: Discussionsupporting
confidence: 62%
“…The hypothesis is based on the sequence similarity of these DR alleles in the third hypervariable region of the DRP chain. Support for this hypothesis has also come from other recent studies of HLA alleles in RA patients (3)(4)(5)44). It is likely that this "epitope" influences binding of peptides to the antigen-binding site in these HLA-DR alleles.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, none of the 150 controls and only 3 of the 198 patients in the present study had "0404; none of our patients had the genotype DRBl "O4O1/*04O4. The most common DRBl allele in the present patient population was "0405, which was also identified in previous cross-sectional studies of Japanese RA patients (21,22). Since the amino acid sequence of the shared epitope of "0404 and "0405 is the same (QRRAA), it would be of interest to examine the contribution of the genotype of "0401/*0405 to the development of bonc erosions.…”
Section: Discussionmentioning
confidence: 92%